Analisis Potensi Ekonomi Pengelolaan Penampungan Sampah Rumah Tangga Berbasis Pemberdayaan Masyarakat di desa Dutohe Barat - Syaiful Pakaya; Syamsul Syamsul (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
Bone Bolango District has taken quite a role in increasing household waste production. Based on the book of the Sanitation Program Memorandum of Bone Bolango Regency, the level of service for handling household waste is 2.5 percent collected and disposed of to the TPS, 97.5 percent is not transported by the Garbage Man (buried, thrown into the river, dumped into empty land, etc.). 86 percent of household waste management is burned and 5.5 percent is disposed of into rivers / sea / lakes. The practice of sorting waste by households is 11 percent sorted and 89 percent not sorted. In 2017, through the local government, a Waste Collection Site (TPS) was built in Dutohe Barat Village, Kabila District, Bonebolango Regency with the aim that the resulting household waste can be processed and provide economic added value for the local community. The results showed that the overall involvement of the community as a whole was still low and the support provided by the village government was still low. The forms of waste management using the TPS3R approach in Dutohe Barat Village have not been running as they should. The economic potential that can be obtained per month is 3,753,120 rupiah. Community involvement is still low due to their minimal knowledge of how to manage household waste, as well as their low willingness to use compost. Meanwhile, the type of inorganic waste which clearly has economic potential is also only done improperly because of the shortage of workers who are willing to be involved.